Susceptibility of human and avian influenza viruses to human and chicken saliva - Nattavatchara Limsuwat (2018)
Oral cavity can be an entry site of influenza virus and saliva is known to contain innate soluble anti-influenza factors. Influenza strains were shown to vary in their susceptibility to those antiviral factors. Whether the susceptibility to the saliva antiviral factors plays any role in the host species specificity of influenza viruses is not known. In this study, the antiviral activity of human and chicken saliva against human and the H5N1 avian influenza viruses were investigated by hemagglutination inhibition (HI) and neutralization (NT) assays. In comparison to human influenza viruses, H5N1 isolates showed reduced susceptibility to human saliva as measured by HI and NT assays. Interestingly, an H5N1 isolate that bind to both α2,3- and α2,6-linked sialic acid showed much higher HI titers with human saliva, suggesting that the susceptibility profile was linked to the receptor-binding preference and the presence of α2,6-linked sialic in human saliva. On the other hand, the H5N1 isolates showed increased HI titers but reduced NT titers to chicken saliva as compared to human influenza isolates. The human salivary antiviral components were characterized by testing the sensitivity to heat, receptor destroying enzyme (RDE), CaCl2/EDTA dependence, and inhibition by mannan, and shown to be α- and γ-inhibitors. These data suggest that the H5N1 HPAI influenza virus had distinctive susceptibility patterns to human and chicken saliva, which may play some roles in its infectivity and transmissibility in these hosts. © 2013 Wiley Periodicals, Inc.